MLVA typing of Mycoplasma hyopneumoniae bacterins and field strains - Tamiozzo, Pablo Jesus (2015)
Because of the lack of information about both the genetic characteristics of Mycoplasma hyopneumoniae commercial vaccines and their relationship with field strains, the authors attempted to identify genetic subtypes of some M hyopneumoniae bacterins, and to compare them with M. hyopneumoniae field strains. Six commercial M hyopneumoniae bacterins and 28 bronchoalveolar lavages from pigs at slaughter from three herds were analysed by Multiple-Locus Variable number tandem repeat Analysis (MLVA) on p146R1, p146R3, H4, H5 and p95 loci. The results obtained showed the presence of more than one M hyopneumoniae genotype in some pigs and also in one of the bacterins analysed. It is also worth noting that MLVA typing allowed the distinction among circulating field strains and also when comparing them with vaccine strains, which, knowing the relatedness among them, could be useful in the research of the efficacy of the vaccines.